2019
DOI: 10.3389/fmicb.2019.00226
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report on the Use of the Design of Experiments for the Production of a Synbiotic Yogurt Supplemented With Gluten FriendlyTM Flour and Bifidobacterium infantis

Abstract: The main goal of this paper was to design a synbiotic yogurt containing Bifidobacterium infantis and Gluten Friendly Flour TM ; the proposed approach relies upon milk fermentation through the classical starter of yogurt ( Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus ) to avoid a strong production of acetic acid by bifidobacterial and inoculum of B. infanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Fortunately, several studies have shown that the foods containing probiotics as live microbial dietary sup-plements have beneficial effects on the prevention and treatment of various gastrointestinal disorders. The antimicrobials produced by probiotics may not only reduce the number of living pathogenic cells but also affect the bacterial metabolism and toxin production [41]. Important mechanisms have also been developed to promote intestinal homeostasis, stabilize or maintain gastrointestinal barrier function, and suppress ROS-induced oxidative stress and carcinogenic enzymatic activities [8].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, several studies have shown that the foods containing probiotics as live microbial dietary sup-plements have beneficial effects on the prevention and treatment of various gastrointestinal disorders. The antimicrobials produced by probiotics may not only reduce the number of living pathogenic cells but also affect the bacterial metabolism and toxin production [41]. Important mechanisms have also been developed to promote intestinal homeostasis, stabilize or maintain gastrointestinal barrier function, and suppress ROS-induced oxidative stress and carcinogenic enzymatic activities [8].…”
Section: Discussionmentioning
confidence: 99%
“…In milk-based beverages, the most frequent applications of MDs aim to improve the rheological, functional, sensory, and antioxidant properties of yogurts and fermented beverages based on milk. Probiotic products were most frequently evaluated, such as yogurt [46,48,49], fermented milk [51], and chocolate beverages [47]. Furthermore, other conventional products, such as yogurt [44,50,55] and dairy drink [57] formulation; yogurt [53] and milk chocolate [45] diet or light; fermented milk [52,56] and soy milk-based beverage [54] have been reported.…”
Section: Application Of Mixture Design In Beveragementioning
confidence: 99%
“…In this works, the authors use MDs for formulations of yogurt or fermented milk symbiotics, probiotics, or organic [46,49,51], with various applications. Such as investigate the influence of starter cultures mixtures for product development [48,55], evaluate the effects of different gums and their interactions on rheological, physicochemical, and sensory properties [44,47,52,56], formulate beverages with low/free sugar content [53,54], formulation of drinks with natural sweeteners [45], fortified with antioxidant [50], or for the formulation of low-cost milk drinks obtained from by-products [57].…”
Section: Application Of Mixture Design In Beveragementioning
confidence: 99%